INTERACTING EFFECTS OF TIME, TEMPERATURE, PH AND SIMPLE SUGARS ON BIOMASS AND TOXIC METABOLITE PRODUCTION BY 3 ALTERNARIA SPP - OZCELIK, S; OZCELIK, N (Springer, 1990)
Biomass and toxic metabolite production by Alternaria hemicota, A. solani and A. tenuis in modified Czapek Dox broth (mCDB) as affected by incubation time (up to 4 wk) temperature (6, 15 and 25.degree. C), pH (3.0, 5.0 and 8.0) and sugars (glucose, fructose and sucrose) was studied. Biomass production was greatest at 25.degree. C and pH 8.0 but toxin production was enhanced at 15.degree. C. In general, biomass production was promoted by up to 9% glucose and sucrose and 6% fructose; however, toxin production was simultaneously reduced by elevated sugars in mCDB over a 4-wk incubation period.